2008
DOI: 10.1158/1541-7786.mcr-07-2184
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Environment Dictates Medulloblastoma Cancer Stem Cell Expression and Invasive Phenotype

Abstract: The neural precursor surface marker CD133 is thought to be enriched in brain cancer stem cells and in radioresistant DAOY medulloblastoma-derived tumor cells. Given that membrane type-1 matrix metalloproteinase (MT1-MMP) expression is a hallmark of highly invasive, radioresistant, and hypoxic brain tumor cells, we sought to determine whether MT1-MMP and other MMPs could regulate the invasive phenotype of CD133(+) DAOY cells. We found that when DAOY medulloblastoma or U87 glioblastoma cells were implanted in nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 57 publications
5
58
0
1
Order By: Relevance
“…In this study, we showed that EGF þ bFGF induce the expansion of CD133 þ BTSCs as gliospheres in culture. Recent studies have shown that tumour environment dictates cancer stem cell expression and invasive phenotype in vivo (Annabi et al, 2008). Although the exact mechanisms are not known, it is most likely that the growth factors induce the expansion of CD133 þ BTSCs or de-differentiation of glioblastoma cells to CD133 þ BTSCs in culture (Kondo, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we showed that EGF þ bFGF induce the expansion of CD133 þ BTSCs as gliospheres in culture. Recent studies have shown that tumour environment dictates cancer stem cell expression and invasive phenotype in vivo (Annabi et al, 2008). Although the exact mechanisms are not known, it is most likely that the growth factors induce the expansion of CD133 þ BTSCs or de-differentiation of glioblastoma cells to CD133 þ BTSCs in culture (Kondo, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In this heterogeneous tumor, CD133À cells in long-term culture were found to be capable of tumor initiation in mice (Chen et al, 2010), although many recent publications maintain that not only is the CD133 þ fraction enriched in BTIC capacity Yan et al, 2011), but the features of 'stemness' marked by CD133 are associated with increasing malignancy and poor patient outcome (Bao et al, 2006;Thon et al, 2008;McCord et al, 2009;Pallini et al, 2010). In medulloblastoma, evidence more uniformly supports the application of CD133 as a BTIC marker, as CD133 þ multipotent NSCs were described in the postnatal cerebellum (Lee et al, 2005), and further studies showed that CD133 enriched for brain tumor-initiating capacity and radioresistance in primary and Daoy medulloblastoma-derived tumors (Fan et al, 2006;Blazek et al, 2007;Annabi et al, 2008Annabi et al, , 2010Pistollato et al, 2010;Yu et al, 2010). In contrast to previous experiments performed on unsorted cells, we found a differential expression of Hh pathway components between the CD133 þ stem-like cells and the CD133À late progenitors or differentiated cells.…”
Section: Shh Regulates Bmi1 In Medulloblastoma Bticsmentioning
confidence: 99%
“…Retrospective analyses of samples from individuals with cancer have revealed that expression of MMPs, such as MT1-MMP and MMP-1, -2, -3, -7, -9 and -13 is positively associated with tumour progression and metastasis, and MMP expression is therefore considered to be a valuable prognostic factor (Deryugina and Quigley, 2006;Hofmann et al, 2005). In addition, MT1-MMP promotes tumour growth and local invasion in a confined three-dimensional (3D) ECM environment (Hotary et al, 2003), and is a key factor in the high infiltration capacity of the brain tumours glioblastoma and medulloblastoma (Annabi et al, 2008;Belien et al, 1999). Most interestingly, MT1-MMP and MMP-2 were shown to accumulate at the invasive front of tumours (Hofmann et al, 2003;Ueno et al, 1997).…”
Section: Introductionmentioning
confidence: 99%